IMPACT ASSESSMENT OF DOMESTIC VIOLENCE AGAINST WOMEN: A CASE STUDY OF DISTRICT FAISALABAD - Dr. Shazia Ramzan; Dr. Shahida Parveen; Ainee Rubab (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Domestic Violence has been the most heinous crime to the well being of the society. In the past, domestic abuse was considered as a private matter and no intervention was thus made by the society. However, sociologists later realized that it is an offence that acts to the detriment of the society as a whole. The state of affairs in Pakistan is not hunky dory in this regard. Pakistan has been ranking in lower quarters among the comity of nations in the indices of human and social capital since decades. The short term effects of domestic abuse include psychological trauma, short-term health effects, lack of immunity, gastrointestinal disorders, fatigue, low energy, chronic pain, loss of appetite and eating disorders among others. The long term effects of domestic abuse, reduced self-esteem, poor work performance, adverse implications upon child growth, psychological aberrations in the victims and child upbringing, lack of confidence in the children. The domestic abuse is an anathema to well being of a modern and moderate society and warrant concerted efforts to curb and eliminate the occurrence of such incidents.